2021
DOI: 10.1111/sms.13959
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impairments after ACL injury – Do we know what we are addressing? Experiences from sports physical therapists

Abstract: Psychological impairments can follow an anterior cruciate ligament (ACL) injury and can impact the rehabilitation process. Our aim was to investigate experiences of sports physical therapists (PTs) in addressing psychological impairments in patients after ACL injury. We conducted four focus group interviews with fourteen sports PTs. The PTs’ experiences of working with psychological impairments after ACL injury were summarized in four main categories: (1) “Calling for a guiding light”, where PTs stated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
1
15
0
5
Order By: Relevance
“…Concerning the acquisition of knowledge, the result of the current study revealed that more than half of the studied patients hadn't good level of knowledge regarding anterior cruciate ligament surgeries and sleep hygiene guidelines among the studied groups, before program implementation. This results were agree with Hussein et al,(2020) (36) , Piussi et al,(2021) (37) , reported that the majority of the studied sample had a good knowledge level. Additionally, the result of the current study revealed that more than half of the studied patients had satisfactory level of knowledge regarding anterior cruciate ligament surgeries and sleep hygiene guidelines among the study groups, after program implementation.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the acquisition of knowledge, the result of the current study revealed that more than half of the studied patients hadn't good level of knowledge regarding anterior cruciate ligament surgeries and sleep hygiene guidelines among the studied groups, before program implementation. This results were agree with Hussein et al,(2020) (36) , Piussi et al,(2021) (37) , reported that the majority of the studied sample had a good knowledge level. Additionally, the result of the current study revealed that more than half of the studied patients had satisfactory level of knowledge regarding anterior cruciate ligament surgeries and sleep hygiene guidelines among the study groups, after program implementation.…”
Section: Discussionsupporting
confidence: 92%
“…Even though a recent consensus statement article concludes that psychological factors play an important role in return to sport, it remains unclear if psychological scales can be used to capture this and improve the rehabilitation process [ 34 ]. Thereto, a study by Piussi et al 2021 suggested that physiotherapists express insufficient knowledge of how to address psychological impairments during rehabilitation [ 35 ]. Our result can provide guidance of important aspects for screening, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Gerade Letzteres wird von vielen Patient*innen als Schlüssel für eine erfolgreiche Rehabilitation angesehen und muss nicht zwangsläufig durch die Rückkehr in den Sport definiert sein. In manchen Fällen kommt es zu einer Neubewertung der eigenen Situation und Identität, und andere Lebensziele werden in den Mittelpunkt gestellt 36 , 57 , 60 , 77 .…”
Section: Psychologische Reaktion Nach Einem Traumaunclassified